The Fourth Tube of the Elbe-Tunnel—Built by the World’s Largest Soft Ground Tunnelling Machine - Claus Becker (Society for Mining, Metallurgy & Exploration, 2001)
The new, 2.600 m long pipe under the river Elbe in Hamburg/Germany required for 2 traffic lanes, emergency lane and space for utilities a boring diameter of 14,20 m(46,6 ft). According the geology (glacial deposits consisting of clay, sand and marl, all containing big boulders) a Slurry-Shield with crusher was selected. With a minimum cover of 7 m and a maximum pressure of 5,6 bar extensive ground treatment was necessary to make the drive feasible. The machine contains a lot of new developments. The drive was finished in spring 2000 so all experiences can be reported. A special risk sharing contract avoided completely litigation.